Industrial Structural Change and Economic Growth in China, 1987–2008. (March 2015) - Zhao, Jingfeng; Tang, Jianmin
Abstract: The present paper studies the sources of economic growth and the nature of structural change in the Chinese economy from 1987 to 2008. Using a methodology that evaluates the contribution of an industry to economic growth, the present paper shows that the post‐2000 subperiod marked an increased reliance on the services sector as a source of growth in the Chinese economy. Much of the acceleration in real GDP or aggregate labor productivity growth in China in the post‐2000 subperiod compared to the pre‐2000 period can be traced to an increased contribution from service‐producing and high‐technology exporting manufacturing industries. The evidence indicates that the Chinese economy has been rebalancing toward domestic consumption and shifting its export sector toward high‐technology manufacturing industries.